ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INDONESIA SUSTAINABILITY REPORTING AWARD (ISRA) (Studi Kasus Pada Perusahaan BEI Peraih Penghargaan ISRA 2013-2016) - Meilana Panjaitan (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2020)
How is the influence ISRA announcement to the abnormal return and the stock trading volume in 2013-2016 on the award-winning companies of ISRA which is the purpose of this research. The method of data analysis used is t-test, with variable X1 (ISRA annaouncement) to Y1 (abnormal return) and Y2 (stock trading volume). The result obtained that tcount value of abnormal return (Y1) amounted 0,896 with significant value amounted 0,073 bigger than level of significant ? = 0,05 so can be concluded sehingga H1 accepted which means there is no significant differences abnormal return. Meaningly that abnormal return with no differences to the award-winning and the non award-winning. The result obtained that tcount value of stock trading volume (Y2) amounted 8,641 with significant value amounted 0,000 bigger than level of significant ? = 0,05. So concluded H1 accepted means there is no significant differences stock trading volume. Meaningly that stock trading volume with no differences to the award- winning and the non award-winning.